Diabetes and congenital malformations. Cienfuegos, 2005-2015 - Oramis Isabel Padrón Aguilera; Maylé Santos Solí; Vivian Rosa Vázquez Martínez; Cristóbal Jorge Torres González; Gladys Bárbara Barberis Pérez (Medisur, 2019)
Foundation: diabetes is the metabolic disorder with the greatest impact on maternal health and its offspring, with greater emphasis on congenital malformations. Objective: to describe congenital malformations in children of diabetic mothers in the province of Cienfuegos. Methods: case series study conducted in Cienfuegos, from January 2005 to December 2015, on fetuses and neonates with congenital malformations, children of diabetic mothers. The data were obtained from the model of the Cuban Registry of Congenital and Prenatal Malformations and other documents of the archives department of the Maternity Hospital of Cienfuegos and the Provincial Center of Medical Genetics. We analyzed socio- demographic, maternal variables, type of malformation and pre and postnatal diagnosis according to the case. Results: the incidence of malformations in children of diabetic mothers was 3.4%; Major malformations predominated, including cardiovascular malformations. There were no differences in the appearance of malformations between pre-gestational and gestational diabetes mellitus. The most frequent risk factors were: maternal overweight, non-communicable diseases and the use of drugs in pregnancy. Conclusions: congenital cardiovascular malformations predominated in children of diabetic mothers and were related to overweight and maternal comorbidity